E-Banking as a Competitive Advantage Driver in Commercial Banks: A Systematic Literature Review - Atmalisa Nurhaliza, Nova (Journal of Banks and Financial Institutions, 2025)
Objective: This study aims to provide a comprehensive overview of how e-banking contributes to the competitive advantage of commercial banks in the digital era. Research Design & Methods: A systematic literature review was conducted using the PRISMA approach, focusing on peer-reviewed articles published between 2020 and 2024. Of the 949 articles screened, 10 studies met the inclusion criteria and were analysed in depth. Findings: The findings reveal that e-banking plays a strategic role in improving operational efficiency, reducing transaction costs, and increasing the speed of service delivery. It also increases customer satisfaction through convenience, accessibility, and 24/7 service availability. Furthermore, e-banking enables market expansion by reaching out to underserved populations. However, limited digital infrastructure, cybersecurity threats, and low user literacy remain critical challenges. Implications & Recommendations: Commercial banks should adopt a holistic e-banking strategy that includes robust cybersecurity measures, transparent customer communication, and continuous innovation. Addressing these areas will help maximise the long-term benefits of e-banking and ensure resilience in a dynamic digital environment. Contribution & Value Added: This study summarizes current insights from international literature and offers strategic guidance for banks looking to leverage e-banking as a sustainable competitive advantage in the financial services sector.